Evolution and present situation of Traditional Chinese Medicine nursing technology (中医护理技术沿革及应用现状) - WANG Yali (王亚丽); WEI Yongchun (魏永春); DONG Yuxi (董玉霞); JIANG Jing (姜婧); E Haiyan (鄂海燕); TANG Ling (唐玲) (Journal of International Translational Medicine Limited, 2023)
Traditional Chinese medicine (TCM) nursing technology has a history of more than one thousand years, and it has rich content and wide practicability. In ancient times, Medical scientists combined medical knowledge and experience of medicine, medicine and nursing, and gained rich experience in TCM nursing technology in practice. With the development of TCM, the operation of TCM nursing technology is more scientific and standardized. According to the clue of development of TCM, this paper summarized the development history of TCM nursing technology, and provided ideas for the inheritance and innovation of TCM nursing technology. (中医护理技术具有千年的历史, 有着丰富的内容和广泛的实用性。在中医实践中, 历代医学家集医、药、护多方面医学知识和经验于一身, 并在行医实践中取得了丰富的中医护理技术经验。随着中医学的发展, 中医护理技术操作更加科学化、规范化、标准化。本文按照中医发展脉络和线索, 对中医护理技术的发展史进行概括论述, 为实现中医护理技术的传承与创新研究提供思路。)